Interface mediated semiconducting to metallic like transition in ultrathin Bi2Se3 films on (100) SrTiO3 grown by molecular beam epitaxy. Issue 107 (19th October 2015) - Debnath, Anil K.; Prasad, R.; Singh, Ajay; Samanta, Soumen; Kumar, Ashwini; Bohra, Anil; Bhattacharya, Debarati; Basu, Saibal; Joshi, Niraj; Aswal, Dinesh K.; Gupta, S. K.
Abstract : Compressive strains due to the structural phase transition of SrTiO3 substrate facilitate semiconductor to metal like transition in Bi2 Se3 thin films. Abstract : Bismuth selenide (Bi2 Se3 ) thin films of nominal thickness ∼10 nm were grown on (100) SrTiO3 and (100) LaAlO3 single crystal substrates using molecular beam epitaxy and their charge transport properties were investigated in the temperature range of 1.5 K–300 K. Bi2 Se3 films deposited on (100) LaAlO3 exhibit semiconducting behavior, while films prepared on (100) SrTiO3 exhibited an anomalous semiconductor-to-metal-like transition at 68 K. The low temperature metal like transition is attributed to compressive strains arising due to structural phase transition of SrTiO3 substrate, which modulate the Bi2 Se3 grain boundary width and facilitate the electric field assisted tunneling of charge carrier at the grain boundaries. The field assisted tunneling of charge carriers is supported by the inverse square-root field dependence of electrical conductivity.